2019
DOI: 10.3390/nu11091976
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in Lactoferrin Levels between Metabolically Healthy and Unhealthy Obese Women

Abstract: Background: The aim of the study was to compare serum lactoferrin concentrations in metabolically healthy obese (MHO) and metabolically unhealthy obese (MUHO) women. Methods: Three hundred (101 MHO and 199 MUHO) women were recruited to the study. Basic anthropometric parameters and blood pressure were measured. Body mass index (BMI) was calculated. Fat mass and visceral adipose tissue mass were assessed using dual X-ray absorptiometry scan. Fasting glucose, insulin, lipid profile, high sensitivity C-reactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Individuals in the MU and MH groups had significant differences in their anthropometric parameters. These differences are due to the MU/MH classification criteria, which introduces a bias so that MU patients have increased metabolic indicators in general, and are consistent with the findings of previous studies [22,76,77]. We also found the MHNO individuals to be younger than their unhealthy pairs, consistently with the fact that the prevalence of metabolic disease increases with age [78].…”
Section: Metabolic Disease Markers In a Crcsupporting
confidence: 91%
“…Individuals in the MU and MH groups had significant differences in their anthropometric parameters. These differences are due to the MU/MH classification criteria, which introduces a bias so that MU patients have increased metabolic indicators in general, and are consistent with the findings of previous studies [22,76,77]. We also found the MHNO individuals to be younger than their unhealthy pairs, consistently with the fact that the prevalence of metabolic disease increases with age [78].…”
Section: Metabolic Disease Markers In a Crcsupporting
confidence: 91%
“…We found similar hsCRP levels between MHO and MUO group, which differed significantly to MHNO, and the association of numbers of MetS components with serum hsCRP began no more significant in the model additionally adjusted for obesity indicators. Studies conducted in Mitchelstown cohort participants, 43 Wielkopolska general population 44 and a large sample of Brazilian population 23 all reported a similar level of CRP between MHO and MUO group. A study using six sets of criteria to define MHO found no significant difference of CRP with MUO subjects after multivariate analysis.…”
Section: Discussionmentioning
confidence: 88%
“…We found similar hsCRP levels between MHO and MUO group, which differed signi cantly to MHNO, and the association of numbers of MetS components with serum hsCRP began no more signi cant in the model additionally adjusted for obesity indicators. Studies conducted in Mitchelstown cohort participants (41), Wielkopolska general population (42) and a large sample of Brazilian population (22) all reported a similar level of CRP between MHO and MUO group. A study using six sets of criteria to de ne MHO found no signi cant difference of CRP with MUO subjects after multivariate analysis (43).…”
Section: Within Twin-pair Analysismentioning
confidence: 87%